Formation of Ukrainian-language competence of foreign medical students in the cultural and educational space of a higher education institution - Семеног, О.; Левенок, І. (Teaching Languages at Higher Educational Establishments at the Present Stage. Intersubject Relations, 2021)
The purpose of teaching Ukrainian to English-speaking medical students is to promote their ability to have professional communication in the Ukrainian language in the cultural and educational space of higher education, as well as during their medical practice. To a large extent, the effectiveness of such communication is stimulated by interdepartmental projects.Based on the analysis, generalization of scientific sources, and educational practice, the article outlines the peculiarities of the formation of Ukrainian-language competence of foreign medical students through involvement in an interdepartmental project on academic culture and information literacy.Terminological analysis, generalization of research, and educational practice gave grounds to clarify the essence of Ukrainian-language competence of a foreign medical student as a professionally important integrative quality of a foreign student’s personality, which allows the applicant to effectively communicate in Ukrainian in the educational and socio-cultural environment.We consider the formation of Ukrainian-language competence of foreign medical students in the cultural and educational space of higher education as a competence-oriented educational process that takes into account, in particular, personality-oriented, communicative, competence approaches and principles of student-centered learning, multifunctionality of the Ukrainian language education, training, and development, as well as intercultural peculiarities, connection with a native language, intercultural dialogue, and personal orientation.The process of effective communicative and pedagogical interaction of foreign students and teachers-mentors in the cultural and educational environment of an institution is stimulated by interdepartmental projects on the formation of the basis of academic culture, integrity, and information literacy. The involvement of English-speaking students of Sumy State University Medical Faculty in research projects provided an opportunity to give practical assistance to the students in developing skills to use good quality information about Ukraine, history, culture, traditions of the city, university, to encourage practical skills of tolerant communication in cross-cultural discussion classes, round tables, during scientific and practical conferences, to promote awareness of moral and ethical values of the medical profession.